Modelling of Stress in Public Transport - Ergin, Mahmut Esad (International Research Journal of Multidisciplinary Technovation, 2022)
The quality of the public transport system is an important factor in determining passenger travel satisfaction and it leads to a better quality of life. Quality of life depends on the quality of services provided in the city. Satisfaction is strongly related to the perception of the users. Many people use public transport on their everyday trips and this paper investigates how road users perceive the public transportation system and the place of the stress factor in this perception. Furthermore, willingness to pay analysis was also carried out, and the amount of additional charge for a less stressful trip was included as a new variable in the model. The binomial logit model is used as a method in this study. As a result, the trip time and the home-based work trips increase the stress level in travel rises. Stress level affects the perception of public transport users, and therefore, users tend to stay away from the stress.